Feasibility of single question mental health surveillance in chronic disease. Issue 10 (9th June 2022) - White, Mary; Pelly, Rachel; Le, Jane; Dove, Lucy; Connolly, Sarah; Morgan, Alice; Reid, Dave; Haslam, Ric; Hiscock, Harriet
Abstract : Objective: To determine the (1) feasibility and acceptability of administering single question mental health surveillance to carers of children with chronic disease in the inpatient setting and (2) sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of this question to detect 'at risk' children compared with the Strengths and Difficulties Questionnaire (SDQ). Design: Cross-sectional pilot Setting: Day Medical Unit of a tertiary paediatric hospital, 1 April 2021–31 July 2021. Patients: Carers of children aged 2–17 years with chronic medical conditions. Interventions: Caregivers were asked to respond to 'Thinking about your child's mental health over the past 4 weeks, are they thriving/coping/struggling/always overwhelmed?' during the admission process. All carers and children 11–17 years were invited to complete the SDQ. Main outcome measures: Feasibility and acceptability were determined by nursing feedback. Sensitivity, specificity, PPV and NPV were determined by comparing question responses with clinical cut-points on the SDQ. Results: 213 carers responded to the question. Nurses reported that the question was easy (12/14) or moderately easy (2/14) to use and was 'easily understood' (6/14) or 'understood after some explanation' (8/14) for most carers. The question demonstrated a high specificity (0.98)/PPV (0.87) but low sensitivity (0.2) when thriving/coping were considered together whereas when thriving was compared with all other responses the sensitivity increased to 0.7. Conclusions: Single question mental health surveillance appears acceptable to carers and nursing staff and has a high level of specificity for children who are 'struggling' or 'always overwhelmed' versus the SDQ screening measure. Abstract : The introduction of a single mental health screening question to a paediatric chronic illness clinic was feasible and acceptable to staff and families. It was a useful tool to identify those requiring more in depth assessment.